2012
DOI: 10.1177/1532673x12450906
|View full text |Cite
|
Sign up to set email alerts
|

Congressional Endorsements in the Presidential Nomination Process

Abstract: Examining congressional superdelegate endorsements in the 2008 Democratic presidential nomination, the authors show that changes in the political context affected the balance of factors in members’ decisions to endorse Clinton or Obama. Specifically, the national standing of the candidates became increasingly important—and local opinion less important—to Obama endorsements even as constituency views became a stronger influence over Clinton endorsements. The findings reveal how constituency considerations affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Although little research explores surrogate or horse-race appearances by members of Congress, a growing body of research has identified factors that explain why members endorse presidential candidates. In particular, electorally safe House members are more likely to involve themselves in the nomination process to claim credit for helping the party (Anderson 2013; Hasecke, Meinke, and Scott 2012). Therefore, the multivariate analysis includes a measure of the percent won by the member in the most recent election, indicating the competitiveness of the district .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little research explores surrogate or horse-race appearances by members of Congress, a growing body of research has identified factors that explain why members endorse presidential candidates. In particular, electorally safe House members are more likely to involve themselves in the nomination process to claim credit for helping the party (Anderson 2013; Hasecke, Meinke, and Scott 2012). Therefore, the multivariate analysis includes a measure of the percent won by the member in the most recent election, indicating the competitiveness of the district .…”
Section: Methodsmentioning
confidence: 99%
“…This is also complicated by the fact that many Democratic representatives endorsed one of the primary candidates, and as superdelegates were of interest to the media as they might ultimately decide the convention outcome. In 2008, members of Congress balanced reelection goals and district concerns, institutional influence, career goals, the dynamics of the nomination contest, and policy goals in their decision of whom to endorse (Anderson 2013; Hasecke, Meinke, and Scott 2012). However, unlike previous years, gender also predicted endorsement of Clinton, with white women more likely to endorse Clinton than white men (Galdieri, Parsneau, and Granberg-Rademacker 2012).…”
Section: Gender Race and Media Coveragementioning
confidence: 99%
“…That this does not appear to have been the case in any of the seven contested Democratic nominations since the practice was instituted has not tempered the criticisms of individuals-from Gary Hart and Jesse Jackson in the 1980s to Bernie Sanders in 2016-who believe their candidacies were negatively impacted. Nor has academic research indicating that superdelegate endorsements are positively correlated with candidates' votes in the constituency (Hasecke, Meinke, & Scott, 2013;Southwell, 1992) mitigated concerns about superdelegates among political activists. In line with the activists' criticisms is that the representativeness of a state's delegation to the Democratic National Convention is negatively related to the proportion of delegation comprised of superdelegates (Southwell, 1992).…”
Section: Party Rules For Delegate Selectionmentioning
confidence: 99%
“…Superdelegates, on the other hand, view their ex‐officio roles more positively, as serving the best interests of the party and ultimately conforming to popular will, even if they are no more able to assess the ideological location and issue positions of rank‐and‐file partisans in the electorate than are pledged delegates, who are presumably closer to the people (Herrera ). The endorsements from superdelegates who are members of Congress, for example, become more heavily associated with national poll standing over local opinion as the campaign wears on (Hasecke, Meinke, and Scott ). Yet, superdelegates have also been shown to vote in line with their own preferences and maintain those to the convention floor (Southwell ).…”
mentioning
confidence: 99%